Effect of platelet rich-fibrin on alveolar osteitis incidence following surgical removal of impacted mandibular third molars: A comparative study - Ali S. Abdul Kareem; Ali H. Al Hussaini (College of Dentistry/ University of Baghdad, 2019)
Background: Postoperative morbidity after extraction of the impacted mandibular third molar (IMTM) is inevitable. One of the most common postoperative complication is alveolar osteitis (AO) which is a painful non healed socket. Many researches were attempted to prevent the occurrence of AO by introducing and applying a new materials inside the extraction socket. Platelet rich fibrin (PRF) is a biological complex fibrin matrix where autologous platelets and leucocytes are present, used to enhance tissue healing process and reduce the early adverse effects of the inflammation. Aims: To evaluate the effect of PRF on the incidence of AO. Also to assess PRF effect on pain, swelling, and trismus following the surgical removal of IMTM and compare it with the control group. Materials and methods: This clinical prospective study was conducted from October 2016 to October 2017 at the Department of Oral & Maxillofacial Surgery, College of dentistry/University of Baghdad; and Al-Sadr Specialized Health Center. A total number of 50 IMTMs were surgically removed from 45 patients who met the inclusion criteria (21 males and 24 females) with age ranged from 16-41 years. The cases were divided into two groups: a study group (25 cases) where PRF were placed inside the extraction socket and control group (25 cases) where traditional surgery were performed. AO, trismus and swelling were assessed at the 2nd and 7th postoperative day. Pain scored by numeric rating scale daily by the patients. Results: The study showed that age, gender, side of impaction, oral hygiene condition, impacted tooth classification, surgical difficulty, and the time of procedure in both control and study groups had nearly similar distribution with non- significant difference. At the 1st follow up period: Trismus (P-value = 0.834) and Swelling (P-value = 0.592) were non- significant between the two groups. AO had overall incidence of 4% occurred only in the control group, while the PRF group had no occurrence (0%), but the difference was statistically non significant. Postoperative pain had no significance difference in both groups. At the 2nd follow up period there was no significant difference regarding trismus, swelling, and incidence of AO between both groups. Conclusion: Local application of PRF can reduce the incidence of AO but not to a significant level. PRF had no effect concerning postoperative pain, swelling, and trismus.